Strategies to increase the survivability of steel connections in fire. (December 2020) - Safari, Pouria; Broujerdian, Vahid
Abstract: This paper aims to investigate and evaluate various strategies to increase the survivability of steel frames exposed to fire conditions using finite element method. Five typical steel connections commonly used in construction were studied, and two series of parametric study were performed so as to assess various fire rehabilitation strategies considering each connection type. The first parametric study investigates the effect of changes in the thickness of elements and type of material, and the second one studies the effect of adding stiffeners and extra plates to the steel frame assemblies. The obtained results revealed that increasing the thickness of beam flange and web is a very effective way to augment the time of survivability of steel frames. Other strategies proved to be ineffective or having slight influence on the fire resistance of steel frames with regard to beam deflection. The ideal strategy or the total case in the first parametric study which incorporates all the rehabilitation strategies into one, proved to be by far the best way to increase the resistance time of the steel frame for more than 25 min prior to reaching the limit deflection. The maximum amount of steel utilized in the total case was about 30 kg which is proved to be very effective regarding the additional resistance time provided. To validate the method, the available experimental fire tests of steel frame assemblies restrained with typical steel connections were used as benchmark. Simulated models proved to be in perfect accord with the experimental ones.